Strengthening innovation and Technology policies for SME Development in Albania - Rovena Tahiti; Besa Shahini (Contemporary Economics)
This paper describes the current economic policies in Albania, particularly in the development of innovative SMEs, identifying the key challenges to promoting innovation in the whole economy - and highlighting specific actions where the private sector has the opportunity and is called upon to take a more active role. The purpose of this paper is to serve as a basis for discussion, primarily with Albanian private sector organizations, in order to agree on the key priorities for action to support innovation in Albania and to identify initiatives where these organizations can help catalyze change going forward.